Likes, Constraints, Boredom of online-offline BIPA Students and Teachers based on Teacher Perceptions - Defina, Defina (FKIP Universitas Lampung, 2023)
Online-offline BIPA learners' and teachers' preferences, constraints, and boredom based on teacher perceptions. Purpose: The research aims to describe preferences, energy, feedback, boredom, and constraints and test different teacher-student constraints. Method: The research population is BIPA teachers worldwide, and a sample of 100 people who have taught online-offline and are willing to complete the Google Form. Finding: Teachers and students prefer offline learning. Teachers need energy in offline learning and students in online learning. Student and teacher constraints are low, but more in online learning. Teachers and students experience more boredom in offline learning. The preference for online learning is due to its flexible and attractive media; the obstacle for teachers and students in online learning is an internet connection; the main causes of boredom in online learning are poor connection and long sitting in front of the computer. Conclusion: Offline learning is still preferable, despite much boredom.Keywords: constraints, preferences, boredom, post-pandemic, online-offline BIPA learning.DOI: http://dx.doi.org/10.23960/jpp.v13.i2.202324